2020
DOI: 10.3389/fcell.2020.555409
|View full text |Cite
|
Sign up to set email alerts
|

Natural Compounds and Autophagy: Allies Against Neurodegeneration

Abstract: Prolonging the healthy life span and limiting neurological illness are imperative goals in gerontology. Age-related neurodegeneration is progressive and leads to severe diseases affecting motility, memory, cognitive function, and social life. To date, no effective treatments are available for neurodegeneration and irreversible neuronal loss. Bioactive phytochemicals could represent a natural alternative to ensure active aging and slow onset of neurodegenerative diseases in elderly patients. Autophagy or macroa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
47
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(47 citation statements)
references
References 269 publications
(299 reference statements)
0
47
0
Order By: Relevance
“…In addition, it has potential anti-cancer and chemopreventive effects. Both in vivo and in vitro studies confirm the effectiveness of PUN in the potential prevention of lung, breast, prostate, and colon cancers [ 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 ].…”
Section: Modulation Of Autophagy In Cancer Cells By Polyphenolsmentioning
confidence: 76%
See 3 more Smart Citations
“…In addition, it has potential anti-cancer and chemopreventive effects. Both in vivo and in vitro studies confirm the effectiveness of PUN in the potential prevention of lung, breast, prostate, and colon cancers [ 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 ].…”
Section: Modulation Of Autophagy In Cancer Cells By Polyphenolsmentioning
confidence: 76%
“…Moreover, they have been suggested to play an important role in the prevention of cancer diseases [ 66 , 71 , 78 ]. The biologically active ingredients of fruits and vegetables, described in this review, such as the main catechin of green tea, EGCG [ 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 ], oleuropein [ 49 , 50 , 51 , 52 , 53 ], punicalgin [ 39 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 ], apigenin [ 40 , 77 , 78 , 79 , 80 ], resveratrol [ …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…At molecular level, it has been suggested that resveratrol acts by inhibiting PDE [ 158 ] and thus increasing the cAMP level culminating in an increase of sirtuin 1 (SIRT1) and PGC1α protein activities which prevents axonal degeneration [ 159 ]. Moreover, resveratrol has been observed to induce the amelioration of mitochondrial activity in some neurodegenerative diseases [ 160 , 161 ].…”
Section: The Camp Signalling In the Regulation Of Mitochondrial Acmentioning
confidence: 99%